2005
DOI: 10.1007/s10674-005-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Different Components of Working Memory to Knowledge Transformation During Writing

Abstract: Outlining probably represents the most common strategy recommended to help novice writers improve their writing. However, although good evidence exists that it has beneficial effects, much less is known about how it achieves these effects. In this paper, we examine how ideas are developed during outlining and how this is related to the quality of the text that is subsequently produced. We focus particularly on how the different processes are coordinated in working memory and on the differences between more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 16 publications
0
55
0
11
Order By: Relevance
“…It follows that manipulating the extent to which high-level problem solving can be carried out during writing should enable the contrasting predictions of the two hypotheses to be tested. Previous research (Galbraith et al, 2005;Kellogg, 1988Kellogg, , 1994) has consistently shown that making an outline before writing leads to improved text quality. It is assumed that this is because separating explicit planning and organizing processes from detailed text production reduces the cognitive load during writing, and enables writers to carry out high-level problem solving more effectively.…”
Section: This Studymentioning
confidence: 96%
See 1 more Smart Citation
“…It follows that manipulating the extent to which high-level problem solving can be carried out during writing should enable the contrasting predictions of the two hypotheses to be tested. Previous research (Galbraith et al, 2005;Kellogg, 1988Kellogg, , 1994) has consistently shown that making an outline before writing leads to improved text quality. It is assumed that this is because separating explicit planning and organizing processes from detailed text production reduces the cognitive load during writing, and enables writers to carry out high-level problem solving more effectively.…”
Section: This Studymentioning
confidence: 96%
“…Previous research has suggested that making an outline before writing enables writers to carry out higher-level problem solving more effectively than when writing is not pre-planned and hence is typically associated with the production of higher quality text (Galbraith, Ford, Walker & Ford, 2005;Kellogg, 1988Kellogg, , 1994. We will argue that the two hypotheses make different predictions about the effect that outlining will have for writers with different writing beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most recommended planning strategy for novice writers is outlining (Galbraith, Ford, Walker, & Ford, 2005;Hayes, 2006). Following Walvoord et al (1995) outlining is the process of producing ''a written vertical list of ideas or information in the sequence that the writer intends for the final piece of writing' ' (p. 400).…”
Section: Outlining As a Planning Strategymentioning
confidence: 99%
“…This type of planning has, broadly, two functions. First, it can facilitate idea generation and retrieval and second, it allows writers to organize and elaborate their ideas into structured arrangements (Englert, Zhao, Dunsmore, Collings, & Wolbers, 2007;Galbraith et al, 2005). It helps a writer to think -at an early stage in the writing process -about the organization and structure of a desired product and/or the steps that need to be followed (Hayes & Nash, 1996).…”
Section: Outlining As a Planning Strategymentioning
confidence: 99%
“…Ennek a kettősfolyamat-modellnek a lényege az, hogy a tudás létrejöttét a szövegben folyamatként fogja fel, amely folyamat az író belső tudásából, illetve a létrehozott kijelentéseinek sorozatából szintetizálódik. Gailbraith, Ford, Walker és Ford (2005) tanulmányaikban bizonyítékot találtak arra is, hogy a vázlatkészítés (outline planning) folyamán a retorikai célok kielégítésére létrehozott új gondolatok magasabb szövegminőséggel járnak, de ezt csökkenthetik a másodlagos feladatok (újragondolás, a szavak előhívása), amelyek terhelik a munkamemória központi végrehajtó és területi komponenseit, így lassítják a folyamatos gondolatmenetet.…”
Section: Az íRásbeli Szövegalkotás Mint Folyamat éS Mint Eredményunclassified